Control of the antiferromagnetic domain configuration and Néel axis orientation with epitaxial strain - Polewczyk, Vincent; Petrov, Aleksandr Yu; Sarpi, Brice; Backes, Dirk; Elnaggar, Hebatalla; Wadhwa, Payal; Filippetti, Alessio; Rossi, Giorgio; Torelli, Piero; Vinai, Giovanni; Maccherozzi, Francesco; Davidson, Bruce A. (Communications materials, 2025)
In the growing field of spintronic devices incorporating antiferromagnetic materials, control of the domain configuration and Néel axis orientation is critical for technological implementations. Here we show by X-ray magnetic linear dichroism in photoelectron emission microscopy how antiferromagnetic properties of LaFeO 3 (LFO) thin films can be tailored through epitaxial strain. LFO films were grown via molecular beam epitaxy with precise stoichiometric control, using substrates that span a range of strain states—from compressive to tensile—and crystal symmetries, including different crystallographic orientations. First, we show that epitaxial strain dictates the Néel axis orientation, shifting it from completely in-plane under compressive strain to completely out-of-plane under tensile strain, regardless of the substrate crystal symmetry. Second, we find that LFO films grown on cubic substrates exhibit a fourfold distribution of antiferromagnetic domains, but can be controlled by varying the substrate miscut, while those on orthorhombic substrates, regardless of strain state, form large-scale monodomains, a highly desirable feature for spintronic applications. Precise control over antiferromagnetic domain configurations and Néel axis orientation is essential for technological advancement of spintronic devices. Here, the authors use epitaxial strain to tailor the magnetic properties of LaFeO 3 thin films, demonstrating a crystal engineering approach which may have much wider applicability.